If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x(x + -6) = 40 Reorder the terms: x(-6 + x) = 40 (-6 * x + x * x) = 40 (-6x + x2) = 40 Solving -6x + x2 = 40 Solving for variable 'x'. Reorder the terms: -40 + -6x + x2 = 40 + -40 Combine like terms: 40 + -40 = 0 -40 + -6x + x2 = 0 Factor a trinomial. (-4 + -1x)(10 + -1x) = 0Subproblem 1
Set the factor '(-4 + -1x)' equal to zero and attempt to solve: Simplifying -4 + -1x = 0 Solving -4 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '4' to each side of the equation. -4 + 4 + -1x = 0 + 4 Combine like terms: -4 + 4 = 0 0 + -1x = 0 + 4 -1x = 0 + 4 Combine like terms: 0 + 4 = 4 -1x = 4 Divide each side by '-1'. x = -4 Simplifying x = -4Subproblem 2
Set the factor '(10 + -1x)' equal to zero and attempt to solve: Simplifying 10 + -1x = 0 Solving 10 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '-10' to each side of the equation. 10 + -10 + -1x = 0 + -10 Combine like terms: 10 + -10 = 0 0 + -1x = 0 + -10 -1x = 0 + -10 Combine like terms: 0 + -10 = -10 -1x = -10 Divide each side by '-1'. x = 10 Simplifying x = 10Solution
x = {-4, 10}
| 40=5x-15 | | 8.4m-0.7-8m=0.22 | | 7x+10=2x-10 | | 2gh+5h-20-8g= | | 4(9.7-8.1)=4(9.7)-4(8.1) | | 5/6(9+2x)=40 | | -.5-1=15 | | 2gh-12h-5g+30= | | 12s+8=4s-2 | | .75p-0.6p= | | 4x^2-20x+23=0 | | 3y-7/5=16 | | 8x+15=3x-15 | | 16+x=y | | 2g-5= | | 0.8z+3.74=z+1.5 | | 4(9.7-8.1)=(9.7)-(8.1) | | 75=3-10t-3+6t | | .75(x-5)=12 | | .5x+1=.5x-1 | | .75w-.50w-4=12 | | 8(x+2)=2(4x+4)+8 | | (-3a^2b^3)(-4a^4b^2)= | | 3(t-1)=9+2 | | 596=-8x | | .75(x+5)=12 | | -9x-21=35x | | m-1=-2-9 | | 5w^2-23w-42=0 | | s=L-rL | | 2x-36=5(x+3) | | 100=20t+5t^2 |